Optimasi Proses Ekstraksi Pektin Dami Buah Nangka (Artocarpus heterophyllus Lamk) - I Nengah Kencana Putra (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
The objective of this research was to determine the optimum condition on extraction process of jackfruit rags pectin. The experiment was designed by Randomized Block Design (RBD) within 3 x 3 factorial experiment. The first factorwas pH of solvent consisted of 3 levels: 1.5, 2.5, and 3,5. The second factor was ratio of jackfruit rags to solvent, con-sisted of 3 levels: 1:5, 1:6 and 1:7. Results repealed that the solvent pH effected significantly yield, total ash, equivalentweigh and anhydrogalacturonic acid content of pectin produced. The optimum conditions for jackfruit rags pectin extraction were: the pH of extracting solvent was 1.5, and the ratio of jackfruit rags to solvent was 1:5. Those condi- tions gave the yield of 4.45 %, produced pectin having total ash (2.82 %), equivalent weigh (3,022.24 g/eqi), methoxylcontent (8.16 %), and anhydrogalacturonic acid content (88.01 %).ABSTRAKPenelitian ini bertujuan untuk menentukan kondisi optimal pada proses ekstraksi pektin dami buah nangka. Rancanganpenelitian yang digunakan adalah Rancangan Acak elompok (RA) dengan pola percobaan faktorial 3 x 3. Faktorpertama adalah pH cairan pengekstrak yang terdiri dari 3 taraf: pH 1,5; 2,5 dan 3,5. Faktor kedua adalah perbandingandami buah nangka dengan cairan pengekstrak yang terdiri dari 3 taraf: 1:5, 1:6 dan 1:7. Hasil penelitian menunjukkan pH cairan pengekstrak berpengaruh nyata terhadap rendemen, kadar abu, berat ekivalen dan kadar asam anhidrogalak- turonat. Kondisi optimal untuk ekstraksi pektin dami buah nangka adalah: cairan pengekstrak pH 1,5, dengan perband- ingan dami nangka dan cairan pengekstrak 1:5. Kondisi ini menghasilkan rendemen 4,54 %, serta pektin dengan kara- kteristik: kadar abu 2,82 %, berat ekivalen 3.022,24 g/eki, kadar metoksil 8,16 % dan kadar asam anhidrogalakturonat88,01 %.